RFID smart attendance system - Mahadi, Mira Elyana; Wan Fauzi, Wan Muhammad Syahmi (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The concept of attendance involves people, either individually or as a group, appearing at a location for a previously scheduled event. The measurement of attendance is of significant concern for many organizations, as such information can be used to gauge the effectiveness of their efforts and to plan for future endeavours. Attendance has traditionally been done manually, fostering student-teacher relationships but prone to errors and time-consuming. The RFID (Radio Frequency Identification) Smart Attendance System project aims to revolutionize the traditional method of tracking attendance by leveraging Radio Frequency Identification (RFID) technology to streamline the process efficiently and accurately. This innovative system seeks to address the problem of time-consuming manual roll calls and the potential for inaccuracies in attendance records. The objective of this project is to develop a user-friendly, automated attendance management system that minimizes human error and maximizes reliability. This project involves integrating RFID tags with an attendance management software, which records each student or employee's attendance as they enter or exit the premises. This system not only simplifies the attendance tracking process but also provides real-time data analytics for better management. By minimizing human intervention, this solution not only streamlines attendance tracking but also strengthens data integrity and operational efficiency.